Civil Servants' Views on The Provision of Additional Income and Its Implications For Work Discipline - Miranda Astuti; Azhar Azhar; Lili Erina (Utan Kayu Publishing, 2025)
The purpose of this study is to explain how Civil Servants (PNS) view the policy of providing additional income and how it impacts work ethics in South Sumatran regional government institutions. This study was conducted using a qualitative approach with a descriptive research type that makes an in-depth analysis of the meaning, perspectives, and experiences of employees. This study involved all civil servants working in South Sumatran regional government institutions, and the sample was selected purposively with 15 informants. After data was collected through documentation, direct observation, and in-depth interviews, the Miles and Huberman interactive analysis model was used to analyze it through the stages of data reduction, data presentation, and drawing conclusions. The results show that most civil servants have a positive opinion about additional income because it is considered to increase motivation, a sense of fairness, and job satisfaction.